Evaluation of the psychometric properties of the Greek version of the Active Life with Asthma (Gr-ALMA) review: a descriptive methodological study - Chris Livadiotis; Ekaterini Lambrinou; Vasilios Raftopoulos; Nicos Middleton (BMC, 2019)
Abstract Background Regular asthma reviews are recommended by international guidelines to improve the quality of life of asthma patients. To facilitate these reviews in primary care practice, there is a need for structured asthma review tools. Aim The aim of this study was to assess the metric properties of the Greek-translated version of the Active Life with Asthma (ALMA) review. Methods A convenience sample of 156 asthmatic patients from three public hospitals participated in this methodological study with a descriptive cross-sectional correlation design. Participants responded to the 19-item ALMA questionnaire and provided socio-demographic and clinical information. The construct validity of the tool was explored in exploratory factor analysis and the internal consistency of scale and sub-scales was estimated using Cronbach's α. Convergence validity was assessed using the Asthma Control Questionnaire (ACQ), a commonly used asthma control measure, and concurrent criterion validity was assessed using the MiniAQoL, an asthma-specific quality of life questionnaire. Known-group validity was assessed based on observed differences in terms of frequency of hospitalizations or emergency visits in the past year. Results Amongst 156 participants, 95 (60.9%) were women and the median age was 50-65 years old. Exploratory factor analysis (KMO = 0.83 and Bartlett test < 0.001) with principal component extraction and orthogonal rotation revealed a clear structure of three factors with little cross-loading: physical, environmental and mental domains, as in the original study. Cronbach's alpha coefficient for internal consistency for the whole scale was 0.85, while for the sub-scales, these were: environmental a = 0.69, mental a = 0.76 and physical a = 0.85. Test-retest reliability based on the correlation between scores of 20 participants responding twice two weeks apart was r = 0.92. There was stong correlation in the expected direction between ALMA and ACQ (r = − 0.70) as well as miniAQoL (r = 0.71). Finally, there were statistically significant higher ALMA scores in participants who reported emergency visits and hospital admissions in the past year. Conclusion In general, the ALMA showed good metric properties. It appears to be a reliable and valid tool which can be used as a measure for asthma control and self-management in clinical practice as well as future descriptive or intervention research studies.